Application of Multi-element Integrated Teaching in the Human Anatomy and Physiology Course in Pharmacy Majors - Zhang, Hong; Xu, Jinghua; Jiahong, Wang; Gu, Yanting; Sun, Guoxiang (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: A professional foundational course in human anatomy and physiology is required of pharmacy students to establish their understanding of the field. Since it includes human anatomy and human physiology, two crucial theoretical courses for medical students, the teaching material for these subjects was employed to adhere to the standards of medical disciplines rather than those of pharmacy. Objectives: This study aimed to establish a multi-element integrated teaching method for human anatomy and physiology to address the training requirements of pharmacy students. Materials and Methods: For pharmacy majors, we designed a multi-element integrated teaching method of human anatomy and physiology from the viewpoints of medicine, pharmacy, and professional ethics. We also summarized the feasibility, significance, and issues associated with multi-element integrated teaching of human anatomy and physiology. Conclusion: Our multi-element integrated teaching method for human anatomy and physiology increased student interest and enhanced the effectiveness of lessons. This approach will promote the development of skilled pharmaceutical workers who are enthusiastic about scientific research and have a sense of social responsibility.
Keywords: Human anatomy and physiology; Pharmacy characteristics; Integrated teaching; Pharmaceutical students growing